Effectiveness of Pre-Harvest Feed Treatments and Post-Harvest Processing in Reducing Escherichia coli Contamination in Catfish (Clarias gariepinus) - Nur Endah Wahyuningsih; Sutopo Patriajati; Ayun Sriatmi; Antono Suryoputro; Puteri Inandin Nabiha; Mahalul Azam (Universitas Airlangga, 2026)
Introduction: The presence of Escherichia coli strains in freshwater fish like catfish (Clarias gariepinus) populations has caused contamination, particularly in Indonesian aquaculture areas where domestic garbage is the primary source of contamination. In order to determine the appropriate handling of E. coli and fecal Coliform contamination before and after harvesting, this study examined the effects of treatment on safety measures for consumption. Methods: Between March and November 2022, a posttest-only control design was used in 126 catfish samples from Bumiayu, Central Java for an experimental study that was quasi-quantitative. There were two types of feed used during growth, followed by six treatments post-harvest (washing; soaking; fry; grill). The MPN method was employed in microbiology testing. Results and Discussion: There was no significant difference in microbial load variation before harvesting the food, with a pre-harvest feed variation of p > 0.05 (indicating that environmental contamination may have been more important). Thermal treatments that completely eradicated E. coli and fecal coliforms (0 MPN/g) by cooking at high temperature for 4-6 minutes and grilling for 5-7 minutes, were the only alternative to post-harvest treatment. Washing and soaking alone remained ineffective. Conclusion: This study demonstrates that high-temperature processing is a reliable method to ensure microbiological safety of catfish, whereas feed variation before harvest has minimal influence under environmentally contaminated conditions. The findings provide practical guidance on safe cooking time–temperature combinations to prevent E. coli exposure from aquaculture products.